IFN-Lambda 3 Mediates Antiviral Protection Against Porcine Epidemic Diarrhea Virus by Inducing a Distinct Antiviral Transcript Profile in Porcine Intestinal Epithelia - Li, Liang; Xue, Mei; Fu, Fang; Yin, Lingdan; Feng, Li; Liu, Pinghuang (Frontiers in Immunology, 2019)
Type III interferon-lambda (IFN-λ) plays a critical role against infection, particularly in mucosal infection in the respiratory and gastrointestinal tract. Our study and other previous studies have shown that porcine IFN-λ more efficiently curtails the infection of porcine epidemic diarrhea virus (PEDV) in the intestine epithelia than type I IFN, whereas IFN-λ3 exerts a more potent effect than IFN-λ1. However, the underlying mechanism remains elusive, and in particular, the transcriptional profile induced by IFN-λ3 has not been reported. Here, to resolve the mechanism responsible for the disparity between IFN-λ3 and type I IFN in anti-mucosal virus infection, we compared the transcription profiles induced by the two IFNs in porcine intestinal epithelial (IPEC-J2) cells by RNA-Seq. Our results showed that the pretreatment of IPEC-J2 cells with IFN-λ3 resulted in the differential expression of 983 genes. In contrast, IFN-α only modified the expression of 134 genes, and 110 of these genes were also observed in the response to IFN-λ3. A transcriptional enrichment analysis indicated that IFN-λ3 or IFN-α regulates multiple cellular processes and that IFN-λ3 activates more robust signaling pathways, particularly the antiviral Jak-STAT signaling pathway, than IFN-α. Furthermore, we verified the RNA-Seq results through an RT-qPCR analysis of IPEC-J2 cells and porcine enteroids. Moreover, transient expression of the porcine rsad2 and mx2 genes among the top 10 genes induced by IFN-λ3 significantly inhibited PEDV infection. Collectively, the data showed that IFN-λ3 induces a unique transcriptional profile that does not completely overlap with that induced by IFN-α and strongly elicits a set of genes responsible for the antiviral activity of IFN-λ3. These findings provide important knowledge regarding the elicited ISGs of type I and III IFNs in restricting porcine intestinal viral infection.